Soccer results affect subjective well-being, but only briefly: A smartphone study during the 2014 FIFA World Cup - Stieger, Stefan; Götz, Friedrich M.; Gehrig, Fabienne (Frontiers in Psychology, 2015)
The current research examined the effects of soccer match results on spectators’ subjective well-being. Across the group stage of the soccer World Cup 2014, German-speaking participants indicated their well-being three times per day through a smartphone-based science app. In line with proposed hypotheses, comparisons of data taken after the three matches of the German national team showed robust effects, revealing that well-being was higher among spectators than non-spectators, with effects increasing as a function of goal difference. Moreover, this gain in well-being was only found in spectators supporting the German soccer team, allowing us to rule out a general emotional contagion effect affecting all spectators. Although soccer results are associated with national identity and pride, their effects on subjective well-being were short-lived and only affected supporters.